The dark triad, dating app use and online disinhibition positively predict technology-facilitated sexual violence perpetration - Gunnoo, Adam (Journal of criminology, 2025)
Technology-Facilitated Sexual Violence (TFSV) describes the perpetration of a variety of sexual offences committed through digital communication technologies. The current study aims to investigate the similarity of risk factors between TFSV and in-person sexual offending. The sample consisted of 105 young adult, Australian males who responded to measures of sexual violence acceptance, dating app usage, online disinhibition, and the dark triad. Overall, 45.3% of the sample reported at least one instance of TFSV perpetration in the past 5 years. Standard and hierarchical linear regressions revealed dating app usage, the dark triad, and online disinhibition positively predicted TFSV perpetration. Neither measure of attitudes accepting of sexual violence predicted TFSV perpetration, but their positive correlation is indicative of cultural norms enabling sexual violence against women. As illuminated here, the congruence between TFSV and in-person violence extends beyond conceptual and prevalence trends to predictive risk factors. Recommendations for interventions and prevention include raising awareness of risk-generating app features that create vulnerability to sexual harm and identifying heterogenous groups of TFSV offenders based on key characteristics to develop optimal intervention strategies.